MO370PREGNANCY-RELATED ACUTE KIDNEY INJURY IN TUNISIA: A CLINICAL CHALLENGE. (29th May 2021) - Msehli, Menel; Jbali, Hela; Ikram, Mami; Ben kaab, Badreddine; Ben hamida, Fethi; Rais, Lamia; BEN FATMA, LILIA; KARIM, ZOUAGHI
Abstract: Background and Aims: Acute kidney injury (AKI) is a complex disorder that occurs in several clinical settings. During pregnancy, there are additional unique conditions that contribute to AKI. The clinical manifestations of Pregnancy related acute kidney injury(PRAKI) range from a minimal elevation in serum creatinine to severe renal failure requiring renal replacement therapy and may be associated with significant morbidity and mortality in young healthy women. This study aims to describe epidemiologic features, study clinical profile and outcomes of women with PRAKI and identify risk factors related to requiring hemodialysis among patients. Method: We performed a retrospective study over a 5-year period (2015–2019) in a Tunisian intensive care unit. All patients presenting PRAKI were included. Results: Ninety-six cases of PRAKI were listed. The rate of AKI during pregnancy-related hospitalizations was 16% .the average age was 31 ± 5 years. Most women were from urban areas (62%) but with insufficient prenatal care (57%).Seventy-eight percent underwent cesarean section delivery. PRAKI occurred in the postpartum in 79%of the cases. Oligo-anuria was the most common clinical feature of PRAKI, noted in 82% of our patients. The leading etiological causes were pre eclampsia, eclampsia, postpartum haemorrhage and sepsis respectively, in 49%, 38%, and 24% of the cases. Hemodialysis was required in 23% of cases. In the adjusted regression analysis, factors associated with dialysis were insufficient prenatal care (p=0, 010 ; O Ra=24, 113), HELLP syndrome (p=0, 003 ; ORa=35, 129), disseminated intravascular coagulation (p=0, 007 ; OR=11, 854), average duration of oliguria (p=0, 001; ORa=3, 025), Failure stage of RIFLE criteria while admitted (p=0, 009; ORa=2, 09) and length of ICU stay (p=0, 042 ; ORa=1, 118). Renal outcome was favorable, with a complete renal function recovery for 72 patients (75%). Only four patients (4%) developed chronic renal failure. Mortality rate was 13%. Conclusion: PRAKI is a dreaded complication of pregnancy with high morbidity and mortality. Prevention of PRAKI requires an improvement of the sanitary infrastructures with the implementation of an obligatory prenatal consultation in order to prompt management of the underlying risk factors